Effects of retting pond wastewater pollution and seasonal variation. (2018) - Arafath, K.A. Yasar; Nilavunesan, D.; Sivanesan, Subramanian; Thiruvengadaravi, K.V.; Baskaralingam, P.
This study focuses on the seasonal variation of physicochemical parameters of coconut husk retting wastewater samples. The main objective of this study is to assess the quality of wastewater during a period of 12 months. The physicochemical parameters such as pH, chemical oxygen demand (COD), biological oxygen demand (BOD), phenol concentration, total solids (TS), total suspended solids (TSS), total dissolved solids (TDS), colour and biodegradability of the wastewater samples were analysed. Most of the analysed parameters were found to be higher than the permissible limit of World Health Organisation (WHO) and Bureau of Indian Standards (BIS) water quality guidelines.